Provenance of zircon xenocrysts in the Neoproterozoic Brauna Kimberlite Field, São Francisco Craton, Brazil: Evidence for a thick Palaeoproterozoic lithosphere beneath the Serrinha block - Donatti-Filho, J.; Oliveira, E.; McNaughton, Neal (Elsevier, 2013)
The 642 Ma-old Brauna Kimberlite Field is located on the northeastern sector of the São Francisco Craton (Serrinha block) and is one of the rare Neoproterozoic kimberlitic events in South America. Zircon xenocrysts from the volumetric most important kimberlite pipes Brauna 03, Brauna 07 and Brauna 04 were used as a tool to identify different components of the lithosphere beneath the northeast region of the São Francisco craton. A composite kimberlite sample of eight representative and different drill holes and three samples of the host rocks (Nordestina granodiorite) were sampled for SHRIMP geochronology. The results were compared with precise U-Pb age data for the regional rocks, i.e. the Archaean basement and the Palaeoproterozoic Rio Itapicuru greenstone belt. Samples from the Nordestina granodiorite gave three different ages: 2155 Ma in the western part of the batholith, 2139 Ma in its central part, and 2132 Ma in its eastern part. Zircon 207Pb/206Pb ages of the Brauna kimberlite zircon grains spread over the timespan 2107-2223 Ma and indicate four age groups at 2105 ± 3 Ma, 2138 ± 7 Ma, 2166 ± 5 Ma, and 2198 ± 4 Ma. Source rocks for the three former age groups can be found in the Rio Itapicuru greenstone belt, including zircon xenocrysts from the Nordestina granodiorite, whereas the latter age group has not yet been reported in the Serrinha block. The new zircon ages show that only rocks of the Palaeoproterozoic Rio Itapicuru greenstone belt and of a hidden 2.17-2.20 Ga crust were sampled by the kimberlite magma during its ascent through the lithosphere. It is proposed that there is none or a few Archaean crust beneath the kimberlite emplacement area, hence implying a thick Palaeoproterozoic lithosphere for this portion of the São Francisco craton.